Comparing carbon and nitrogen stocks in paddy and upland soils: Accumulation, stabilization mechanisms, and environmental drivers - Wei, Liang; Ge, Tida; Zhu, Zhenke; Luo, Yu; Yang, Yuanhe; Xiao, Mouliang; Yan, Zhifeng; Li, Yuhong; Wu, Jinshui; Kuzyakov, Yakov (Geoderma, 2021)
[Display omitted] •Mechanisms of higher C and N stocks in paddies than upland soils are reviewed.•Climate effects on stocks are weakened by management (puddling and flooding).•Larger organic C input in paddies compared to most upland cereals was found.•Lower O2 availability leads to slow decomposition of organic matter in paddies.•Fe and Mn oxidation–reduction dynamics stabilise C in paddy soils. Paddy soils, a type of Hydragric Anthrosol, have much greater soil organic C (SOC) and total N (TN) contents than that in upland soils. However, this fact has never been generalized or mechanistically explained. We conducted a global meta-analysis on the organic C and total N contents and their stocks in continuous paddy soils (578 sites) and compared them with those in adjacent upland soils. Average C stocks up to depths of 35 cm in upland and paddy soils were 31 and 47 Mg C ha−1, respectively. The N stocks in upland and paddy soils were 2.2 and 3.2 Mg N ha−1, respectively. The combined effects of mean annual temperature and precipitation showed that C and N stocks in paddy and upland soils are generally the largest under cool and humid conditions and the smallest in warm and dry climates. Quantitative analysis of climatic, and soil physical and chemical factors showed that 1) climate effects are weakened by management such as puddling and flooding, thereby increasing the importance of soil physico-chemical properties, which control soil organic matter (SOM) stabilization, and 2) climate (e.g., mean annual precipitation) mainly affects C and N stocks in upland soils; the chemical properties (such as pH), on the other hand, primarily affect C and N stocks in paddy soils. Greater C and N stocks in paddy soils are the result of 1) a larger input of organic C by rice than by most upland cereals, 2) slower decomposition of plant residues and SOM under anoxic conditions, and 3) a greater importance of sesquioxides in the biochemical stabilization of SOM. We conclude that these man-made paddy soils store more organic C and N than their upland neighbors despite long-term and intensive management.